Delays by Contractors in Construction of Health Infrastructure and Short Levy of Liquidated Damages in Karnataka - CAG of India (CAG of India)
The Chief Engineer, Health Engineering Wing levied nominal penalty for delays on part of the contractors in completing the works based on the recommendations of the Executive Engineers of the divisions. This resulted in short levy of liquidated damages of ₹ 14.63 crore besides extending undue benefit to the contractors.